UPAYA MENINGKATKAN KEMAMPUAN BERBAHASA PADA PEMBELAJARAN AFIKSASI SISWA KELAS V SDN 01 UJAN MAS DENGAN MENERAPKAN METODE DISCOVERY - Ahmad Ses (Universitas Bengkulu, 2018)
Learning is an urgent matters in the world of education, because it is something that is important and urgent that require immediate decisions and actions. This action research was conducted to obtain answers on issues related to learning affixation by using Discovery on the class of fifth grade students of SD Negeri 01 Ujan Mas Kepahiang District Bengkulu. The series of activities classroom action research was conducted in two cycles and sitiap cycle consists of: (l) action plan (2) action, (3) observation, and (4) reflection. Application of discovery learning methods in learning affixation ber-kan and ber - an in Class V SD Negeri 01 Ujan Mas can improve and enhance the activity of the learning process students having mastered the learning material showed an increase. This can be shown by the average result of the acquisition of 57 in the first cycle increased to 77 in the second cycle, from the observation of increased activity of students in the first cycle obtain the average - average 57% increased to 77%. Interviews conducted entirely student said he was happy and liked the discovery learning method. Based on the above results we can conclude that the working hypothesis that the author interchanges that if the affixation ber-kan and ber - an implemented by the method of discovery will require students to learn science with satisfactory results.Keywords: language skills, learning affixation, methods of discovery